How Workers Experience Psychological Well-Being During COVID-19: A Qualitative Study - Bezzaa, Ali; El Yadari, Khalid (Advances in Social Sciences Research Journal, 2022)
This article draws on the theoretical framework of psychological well-being in order to explore the phenomenon of well-being at work during COVID-19. More specifically, this study utilizes a qualitative methodology and both hedonic and eudaimonic perspectives of well-being to make sense of the experience of well-being at work. Through purposeful sampling, we asked thirty-two Moroccan workers to describe to us their latest well-being experiences on the job. Overall, we identified fifty-five well-being incidents. Content analysis allowed us to categorize ten dimensions of psychological well-being at work that meet the assumptions of the theory used: positive emotions, satisfaction with the work environment, meaning of work, self-confidence, work autonomy, desire for commitment, development needs, positive relationships with colleagues, perceived performance, and recognition and organizational quality. These findings are discussed with regard to previous literature along with practical implications, limitations, and future research avenues.